Shifting horizons: Significant life events and pro-environmental behaviour change in early adulthood - Mitev, Kaloyan; Whitmarsh, Lorraine; Gattis, Merideth; Nash, Nicholas (PLOS Climate, 2025)
Young people’s daily routines are especially malleable during significant life events, offering opportunities for pro-environmental behaviour (PEB) change. We investigated how PEBs shifted during two Moments of Change (MoCs), an exogenous disruption (COVID-19) and a biographical transition (starting university). We also looked at whether values and attitudes explained these shifts. We conducted two longitudinal studies with 16–24-year-olds. Study 1 (exogenous MoC) tracked behaviour across three waves during 2020 (n = 146) using multilevel latent growth models. Study 2 (biographical MoC) (n = 256) used paired-samples t-tests examining change across two time points, i.e., pre and post the start of university. Both studies used path-analytic structural equation models to test a values – attitudes – behaviour pathway and regressions to examine the self-activation hypothesis. In Study 1, we found positive changes to food waste and the consumption of animal products, and a negative change in environmental activism and active travel. In Study 2, we found positive changes in domestic PEBs, active travel, and the consumption of animal products, and negative changes in environmental activism and ethical consumption. Self-transcendence values positively predicted activism (Study 1) and domestic PEBs (Study 2) and related to lower animal-product consumption in both studies, while environmental attitudes mediated the link between self-transcendence and consumption only in Study 2. These findings suggest that targeted interventions timed to MoCs can leverage values and attitudes to support lower-impact diets and home practices. Structurally constrained domains (e.g., activism opportunities, infrastructure-dependent travel) may require contextual changes in tandem with MoCs to yield benefits to PEBs. Our study is one of the first to look at COVID-19 as a MoC and one of the first to examine the transition from school to university and its effects on multiple PEBs. Some limitations include reliance on self-report measures with retrospective baselines and short follow-up periods.